Pulses’ benefits in children’s diets: a narrative review - Vieira, Evla D. F. (2022)
Pulses are affordable, environmentally friendly, nutritious foods with a long shelf-life. In particular, they are excellent sources of protein, fiber, minerals, vitamins, and phenolic compounds and can prevent and control chronic diseases. Due to their high nutritional density, consumption of pulses may be significant for children’s development. However, pulses also provide non-nutritional components that have beneficial health effects but that may have a few negative side effects if consumed improperly. The presence of such compounds, and the lack of a clear message about their potential benefits or drawbacks has, historically, influenced the consumption of legumes. The present study aims to provide a literature review of pulses’ benefits in children’s diets. For this purpose, we performed a search in PubMed and ScienceDirect databases of documents from the last 20 years (from 2000-2020), using the following search terms: “legume”, “pulse”, “consumption”, “benefits”, “health”, “nutrition”, “recommendations”, and “children”. Pulses help meet micro-nutrient demands in childhood and should be part of children’s diets since the stage of complementary feed. Also, regular pulses’ consumption may help to reduce childhood obesity and be an effective alternative to control glycemic response in diabetic children. The non-nutrients present in pulses do not represent a risk for Children’s growth, as they are considerably reduced during the usual processing and cooking procedures.